ANALISIS HARGA POKOK PRODUKSI PADA USAHA SUMBER GIZI NABATI DI KOTA PEKANBARU - Uli Yamasari; Makhdalena ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: Determination of cost of goods manufactured is very important in an effort to determine the selling price and profit generated. The purpose of this study is to analyze the calculation of cost of production and differences in calculations made by companies with calculations using the full costing method.This research was conducted on Sumber Gizi Nabati Enterprise. Data obtained through site, surveys and direct interviews with the company concerned with issues discussed and documents as supporting evidence. In addition the authors also collected the necessary data through literature study through the literature in accordance with this study.The result of the research shows that the calculation of cost of production at Sumber Gizi Nabati Enterprise with the calculation of cost of production using Full Costing method shows the difference of results. The difference lies in the factory overhead cost of the Full Costing method which includes the cost of depreciation of machinery and vehicles as well as the cost of maintaining machines and vehicles. This causes the cost of production using the method of Full Costing becomes higher.Key Words: Cost of Production, Full Costing.